The Effect of Using Charcoal Toothpaste on Teeth Color Changes in Adolescents - Khossy’ Afrohhatunnisa; Hadiyat Miko; Rena Setiana Primawati (Journal Center of Excellent : Health Assistive Technology, 2023)
Discoloration is a condition in which the color of the teeth changes due to various causative factors such as physiological and pathological factors or extrinsics and intrinsic factors. Dental dislothesiration treatment one of them can use charcoal toothpaste. Purpose: Knowing the effect of the use of charcoal toothpaste on tooth color changes in adolescents in Pesantren Daarussalam Kawalu Tasikmalaya. Research Methods: This study uses one type of research (Pre-Eksperimental) and one design (One group pre-test and post-test design) The study subjects were as many as 20 people at Pesantren Daarussalam Kawalu Tasikmalaya. The way of research is that researchers take pre-test and post-test data for 21 days of direct examination of respondents' teeth using Shade Guide Vitapan Classical teeth. Data analysis was conducted with the Wilcoxon Signed Ranks statistical test. Results: The results of statistical tests on the effect of using activated charcoal toothpaste (charcoal) on changes in value of 0.000. The hypothesis requirement is accepted, namely <0.05, this shows that there is aninfluence on the use of charcoal toothpaste on tooth color changes in adolescents in Pesantren.